KONTRIBUSI INFORMATION COMMUNICATION AND TECHNOLOGY (ICT) PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract: The development of Information and Communication Technology (ICT) has an important contribution in education, especially in learning process. Shortages and bottlenecks in the learning process can be overcome with the use of ICT. Social studies as one of Sciences relating to the development of human life both in terms of economic, social relations, culture, history, law and its interaction with the natural environment is closely associated with the level of human civilization, including today's technology. All aspects of human life is the object of study in Social studies. Therefore to be able to clarify the learning materials so broad and constantly experiencing these developments, then information and communication technology (ICT) which is now thriving very supportive.Â